RESILIENCE AND HARDINESS: A PROPOSED CONCEPTUAL MODEL FOR HEALTHCARE WORKERS - Nadzrah Yusof; Salmi Mohd Isa; Goh Yen Nee (Journal of Islamic, Social, Economics and Development, 2022)
As the healthcare industry continues to evolve, it is critical that the healthcare workforce in the public hospitals equipped themselves with the necessary skills and resources to deliver effective and efficient care to the stakeholders. This can be done through the development on the job training and continuous resilience coaching for healthcare workers. This paper aims to discuss the various constructs of resilience and hardiness that are used in the development of resilience coaching for healthcare workers. The paper draws on the various literature sources to create a conceptual model for coaching resilience and hardiness among healthcare workers. Healthcare organizations should encourage resilience and hardiness among healthcare workers through various interventions in order to improve their coping techniques and overall well-being. According to the conceptual model that was presented, healthcare organisations should train their staff members to be more resilient and instil a sense of hardiness in them in order to improve the level of patient safety and better deal with the requirements of their profession.